Hexavalent chromium reduction ability and bioremediation potential of Aspergillus flavus CR500 isolated from electroplating wastewater. (December 2019) - Kumar, Vinay; Dwivedi, S.K.
Abstract: Hexavalent chromium reduction by microbes can mitigate the chromium toxicity to the environment. In the present study Cr[VI] tolerant fungal isolate (CR500) was isolated from electroplating wastewater, was able to tolerate 800 mg/L of Cr[VI . Based on the ITS region sequencing, the isolate was identified as Aspergillus flavus CR500, showed multifarious biochemical (reactive oxygen species, antioxidants response and non-protein thiol) and morphological (protrusion less, constriction and swelling/outwards growth in mycelia) response under Cr[VI] stress. Batch experiment was conducted at different Cr[VI] concentration (0–200 mg/L) to optimize the Cr[VI] reduction and removal ability of isolate CR500; results showed 89.1% reduction of Cr[ VI] to Cr[ III] within 24 h and 4.9 ± 0.12 mg of Cr per gram of dried biomass accumulation within 144 h at the concentration of 50 mg/L of Cr[VI] . However, a maximum of 79.4% removal of Cr was recorded at 5 mg/L within 144 h. Fourier-transform infrared spectroscopy, energy dispersive x-ray spectroscopy and X-ray diffraction analysis revealed that chromium removal also happened via adsorption/precipitation on the mycelia surface. Fungus treated and without treated 100 mg/L of Cr[VI] solution was subjected to phytotoxicity test using Vigna radiata seeds and result revealed that A. flavus CR500 successfully detoxified the Cr[VI] via reduction and removal mechanisms. Isolate CR500 also exhibited efficient bioreduction potential at different temperature (20–40 °C), pH (5.0–9.0), heavy metals (As, Cd, Cu, Mn, Ni and Pb), metabolic inhibitors (phenol and EDTA) and in sterilized tannery effluent that make it a potential candidate for Cr[VI] bioremediation. Graphical abstract: Image 1 Highlights: A. flavus CR500 show multifarious biochemical and morphological response to deals with Cr[VI] toxicity. Cr[VI] induced chromate reductase play a major role in the reduction of Cr[VI] to Cr[III] . Accumulation, precipitation and adsorption mechanism involve in Cr removal by isolate CR500. Isolate CR500 has excellent Cr[VI] bioremediation potential.